School grades and students' emotions: Longitudinal models of within-person reciprocal effects. (February 2023) - Pekrun, Reinhard; Marsh, Herbert W.; Suessenbach, Felix; Frenzel, Anne C.; Goetz, Thomas
Abstract: Based on control-value theory, we expected reciprocal associations between school grades and students' achievement emotions. Existing research has employed between-person designs to examine links between grades and emotions, but has failed to analyze their within-person relations. Reanalyzing data used by Pekrun et al. (2017) for between-person analysis, we investigated within-person relations of students' grades and emotions in mathematics over 5 school years ( N = 3, 425 German students from the PALMA longitudinal study; 50.0% female). The findings from random-intercept cross-lagged modeling show that grades positively predicted positive emotions within persons over time. These emotions, in turn, positively predicted grades. Grades were negative predictors of negative emotions, and these emotions, in turn, were negative predictors of grades. The within-person effects were largely equivalent to between-person relations of grades and emotions. Implications for theory, future research, and educational practice are discussed. Highlights: We used latent versions of the random-intercept cross-lagged panel model. Grades showed positive within-person reciprocal links with positive math emotions. Grades showed negative within-person reciprocal links with negative math emotions. Findings document equivalence of within- and between-person relations. Teachers are advised to attend to students' emotions.